2012
DOI: 10.1136/bcr.12.2011.5389
|View full text |Cite
|
Sign up to set email alerts
|

Intraoral schwannoma - a report of two cases

Abstract: Schwannomas, also known as neurilemmomas, are uncommon neoplasms, derived from schwann cells. These neoplasms, although rare, should be considered in the differential diagnosis of slow growing tumour masses of the oral cavity. The growth of these tumours sometimes causes displacement and compression of the nerve of origin, giving rise to clinical signs and symptoms. It can develop at any age and there is no sex predilection. Intraorally, the tongue is the most common site followed by the palate, floor of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…This was in accordance with our study which revealed that 24 patients (55.8%) were presented between 2 nd and 4 th decades. Concerning sex predominance for tongue base schwannomas, Some authors reported that there was no sex difference [12,20,30] , while others claim that there is female predominance (1.6:1) [39] . This was similar to our review that showed higher incidence among females (1.5:1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was in accordance with our study which revealed that 24 patients (55.8%) were presented between 2 nd and 4 th decades. Concerning sex predominance for tongue base schwannomas, Some authors reported that there was no sex difference [12,20,30] , while others claim that there is female predominance (1.6:1) [39] . This was similar to our review that showed higher incidence among females (1.5:1).…”
Section: Discussionmentioning
confidence: 99%
“…Different surgical approaches have been described for tongue base schwannomas. They include trans-oral (robotic surgery, CO2 Laser excision, or using diathermy) [2][3][4][5][6][7][8][9]12,[14][15][16][17]19,[21][22][23][25][26][27][28][29]31,32,34] , submandibular pull-through [13] , suprahyoid (trans-hyoid) lateral pharyngotomy approaches [18,20,24,30,33,34] and midline mandibulotomy and tongue split [10,11] . In our review, we found that most lesions were excised transoral without any significant intra or postoperative morbidities (76.7%).…”
Section: Discussionmentioning
confidence: 99%
“…4 Cerca del 25 al 48% de los casos afecta la región de la cabeza y cuello; en la cavidad oral se observa principalmente en lengua, mucosa bucal y labio. 5 Su anatomía patológica se caracteriza por lesiones só-lidas, subcutáneas y asintomáticas; 6 histológicamente está compuesto por prototipos de organización celular denominados Antoni A y Antoni B.…”
Section: Introductionunclassified
“…4 About 25 to 48% of all cases affect the region of the head and neck; in the oral cavity, it is mainly seen in the tongue, the buccal mucosa, and the lips. 5 Its pathology is characterized by solid, subcutaneous, asymptomatic lesions; 6 histologically it is composed of prototypes of cell organization called Antoni A and Antoni B. 2 The Antoni A region is a hypercellular zone whose cells are fusiform with nuclei arranged in palisade forming parallel rows and producing the Verocay bodies.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies that have separated these entities have shown schwannomas to be the most common benign nerve sheath tumor of the head and neck [2,3]. The clinical features of head and neck schwannomas have been documented in numerous short series [2][3][4][5][6] and case reports, including specific subsites such as the tongue [7][8][9][10], palate and other intraoral locations [11][12][13][14][15][16], and nose, paranasal sinuses, and anterior skull base [17][18][19][20][21][22][23][24][25][26][27][28]. Pathologic details of schwannomas arising in the head and neck are, however, sparsely documented in the literature.…”
Section: Introductionmentioning
confidence: 99%